The Huarochiri Trickster - Medeiros, Sérgio (2017)
The Huarochiri Manuscript holds a summation of native Andean religious tradition and an image of the superhuman and human world as imagined around A.D. 1600. Here one catches a glimpse of the image of god as a trickster (ambiguous creator and destroyer).